2008
DOI: 10.1200/jco.2008.16.7510
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Study of Cilengitide, an Integrin-Targeting Arginine-Glycine-Aspartic Acid Peptide, in Recurrent Glioblastoma Multiforme

Abstract: A B S T R A C T PurposeCilengitide, an inhibitor of ␣v␤3 and ␣v␤5 integrin receptors, demonstrated minimal toxicity and durable activity across a wide range of doses administered to adults with recurrent glioblastoma multiforme (GBM) in a prior phase I study. The current multicenter phase II study was conducted to evaluate the activity and safety of cilengitide in GBM patients at first recurrence. Patients and MethodsEligible patients were randomly assigned to receive either 500 or 2,000 mg of cilengitide twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
298
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(303 citation statements)
references
References 27 publications
4
298
0
1
Order By: Relevance
“…However, the trial design containing a placebocontrolled active control (lomustine+placebo) at least allows reasonable conclusions on activity. The integrin inhibitor cilengitide tested in two dosing regimens in a randomized fashion, without a control arm lacking the experimental agent, showed a trend to prolonged survival at the higher dose [112]. A novel principle, the inhibition of histone deacetylase aiming to target epigenetic gene regulation, with agents such as vorinostat or panobinostat so far failed to provide efficacy signals [89,102,113,114].…”
Section: Targeted Therapymentioning
confidence: 99%
“…However, the trial design containing a placebocontrolled active control (lomustine+placebo) at least allows reasonable conclusions on activity. The integrin inhibitor cilengitide tested in two dosing regimens in a randomized fashion, without a control arm lacking the experimental agent, showed a trend to prolonged survival at the higher dose [112]. A novel principle, the inhibition of histone deacetylase aiming to target epigenetic gene regulation, with agents such as vorinostat or panobinostat so far failed to provide efficacy signals [89,102,113,114].…”
Section: Targeted Therapymentioning
confidence: 99%
“…Etaracizumab is a monoclonal antibody to α V β 3 that is undergoing early clinical development for treatment of melanoma [59][60] and solid tumours 61 . The cyclic-RGD peptide cilengitide is a specific α V β 3 antagonist and is currently under going clinical trials for use in glioblastoma [62][63] and in other brain cancers 64 and has recently become the first anti-integrin to enter Phase III trials for cancer 65 . The orally-active, non-peptide α V β 3 antagonist MK 0429 is under going clinical development for prostate cancer 66 .…”
Section: Integrins and Diseasementioning
confidence: 99%
“…8,9,[44][45][46][47][48] It is therefore plausible that inhibiting aVintegrin-ligand interaction should reduce tumor progression. As a single agent, cilengitide inhibits growth of brain tumors 23 and has modest activity in recurrent clinical glioblastoma, 36 an activity which appears to be amplified by co-therapy with ionizing radiation. 25,49 In the present study, as in others such as that of Mikkelsen et al, 25 cilengitide alone did not reduce tumor growth but it is possible that this was because our model involved only a single short exposure to the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Cilengitide is currently under active investigation as a systemic agent in randomized phase II and phase III clinical trials in tumors including squamous cell cancer of the head and neck and glioblastoma, [32][33][34][35] in which antitumor activity has been reported. 36 To complement our in vivo ILP studies in sarcoma and explore possible mechanisms of action underlying the phenomena observed, we carried out a series of in vitro experiments investigating the effects of cilengitide on BN175 cell adhesion and endothelial permeability. Such effects may account for the increased tumor response rates seen.…”
mentioning
confidence: 99%